The influence of post-harvest treatments on the coppice response of two woody savanna species - Rankin, Christopher James (My University, 2017)
Fuelwood is still heavily relied upon by rural communities as a source of energy. The current levels of wood harvesting have been deemed unsustainable, with models predicting the local exhaustion of wood resources in most cases. However, wood depletion has generally not happened to the level of severity predicted by the models. This may partially due to under-accounting for coppice regeneration. Many savanna species that are harvested for fuelwood demonstrate strong coppicing ability, which allows for regrowth after a disturbance. This ability to regrow or coppice is a key functional trait which allows species to persist and survive in frequently disturbed environments. There is surprisingly limited knowledge about coppice dynamics in savanna trees and how managerial actions might influence the coppice response and production of savanna species. To address this problem, this study investigated the influence of four post-harvest treatments on various aspects of the coppice response of Terminalia sericea and Dichrostachys cinerea – two important savanna fuelwood species – in a field experiment. A total of 108 felled trees per species were exposed to one of four treatments, which were applied monthly for 12 months. The treatments were (1) Control – no coppice shoots were removed for 12 months, (2) Harvest – all coppice shots were removed monthly, (3) Single prune – the coppice shoot with the widest diameter was left on the stump, and (4) Usable – coppice shoots that reached a diameter of 2 cm were removed. The effect that these treatments had on the average diameter, length and cumulative number of coppice shoots produced per stump was compared. The measurements of diameter and length were used in developing allometric equations for the prediction of coppice shoot biomass. The predicted biomass produced through the study was compared across treatments to gain an understanding of how productivity could be influenced by management of coppice shoots. The mean shoot diameter, length, as well as cumulative number of coppice shoots produced per stump was higher in the single prune treatment for both species while the harvest treatment resulted in high numbers of coppice shoots but with low average diameter and length. Applying the growth rates of coppice shoots found in this study it can be assumed that unmanaged coppice shoots will take approximately 5.5 years to reach a preferred harvestable diameter of 4 cm, while single prune coppice shoots would take 3.3 years to reach the preferred harvestable diameter. Diameter had more of an influence on the predicted coppice biomass production of T. sericea while D. cinerea biomass prediction was more influenced by shoot length. However, only diameter was used to compare the prediction of coppice biomass with previously developed equations as these equations did not consider length for predicting biomass of different components of trees. From the derived models, the calculated biomass at the end of the study period as well as the calculated biomass produced through the year was greatest for the control treatment. The predicted dry shoot stem biomass at the harvestable diameter of 4 cm was 114.60 g for T. sericea and 95.88 g for D. cinerea. From the findings of this study it is clear that post-harvest management can be utilised to manipulate coppice response and biomass production. Keywords: Fuelwood; Coppice shoot; Post-harvest treatment; Diameter; Length; Biomass
A dissertation submitted to the Faculty of Science, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Science, Johannesburg, South Africa 2017.
Keywords: Fuelwood crops--South Africa; Savanna plants; Savanna ecology